The Implementation of Diet Therapy for Autistic Students - Elisa Citra Anisa; Sudarsini Sudarsini; Sulthoni Sulthoni (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2020)
Autistic children tend to experience digestive disorders. Therefore, autistic children must take diet therapy. This research used qualitative method. The results showed that (1) Implementation of diet therapy: preparation, implementation, monitoring and evaluation. (2) Obstacles in the implementation of diet therapy: autistic students themselves, parents, and the difficulty of getting certain food. (3) Impact of diet therapy: students are more silent and can sit quietly during the implementation of ABA therapy. The implementation of diet therapy for autistic students will have a good impact if applied correctly. Suggestions in this research, do not let a diet leak even if only once.